2016
DOI: 10.11152/mu.2013.2066.183.joo
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of on-site education for quality assurance of screening ultrasonography for hepatocellular carcinoma

Abstract: Objective: To evaluate the usefulness of on-site education for clinical imaging evaluation using quality assurance (QA) testing of surveillance ultrasonography (US) for hepatocellular carcinoma (HCC). Material and methods: Thirty-eight medical institutes underwent on-site education in 2012 for QA testing of clinical imaging evaluation of surveillance US for HCC. Failure rates and mean scores of clinical imaging evaluation for surveillance US of the 2011 survey, the 2012 survey after onsite education and the 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
0
1
0
6
Order By: Relevance
“…Son et al [40] reported that the US-3 category demonstrated high specificity, but low sensitivity, for diagnosing HCC and that the visualization score C had a higher false-negative rate than scores A or B. Kang et al [41] reported a high diagnostic yield of US-guided biopsies with visualization scores of A (91.1%) or B (74.5%), but not for those with a score of C (42.9%). In Korea, the US experts of Korean Society of Ultrasound in Medicine are working on standardizing the US scanning protocol for HCC surveillance and educating physicians under the Korean National Cancer Screening Program [42][43][44].…”
Section: Representative Examples Of the Ultrasound Liver Imaging Reporting And Data System (Us Li-rads)mentioning
confidence: 99%
“…Son et al [40] reported that the US-3 category demonstrated high specificity, but low sensitivity, for diagnosing HCC and that the visualization score C had a higher false-negative rate than scores A or B. Kang et al [41] reported a high diagnostic yield of US-guided biopsies with visualization scores of A (91.1%) or B (74.5%), but not for those with a score of C (42.9%). In Korea, the US experts of Korean Society of Ultrasound in Medicine are working on standardizing the US scanning protocol for HCC surveillance and educating physicians under the Korean National Cancer Screening Program [42][43][44].…”
Section: Representative Examples Of the Ultrasound Liver Imaging Reporting And Data System (Us Li-rads)mentioning
confidence: 99%
“…Ainda há escassez de material publicado na literatura sobre esse tema. Embora tenham sido publicados trabalhos sobre as características técnicas dos equipamentos (10,11) , sobre o treinamento no método (12) e sobre a influência da qualidade das imagens em determinados diagnósticos (13)(14)(15) , um dos poucos artigos escritos nesta linha, foi o método proposto por este grupo, batizado de SQUALUS -Sistema Quantitativo de Avaliação da Qualidade de exames Ultrassonográficos. (16) Pelo método proposto no artigo original, a avaliação da qualidade das imagens documentadas verificava inicialmente se o número de imagens e estruturas registradas seguiram protocolos pré-determinados por órgãos como o Colégio Brasileiro de Radiologia (CBR) ou pelo American College of Radiology (ACR) ou ainda pelo American Institute of Ultrasound in Medicine (AIUM).…”
Section: Introductionunclassified
“…Fator de risco 13,27,29,114 Força muscular respiratória 12,13,14,17,19,21 O Obesidade 23,28,31,38,39,40,56,102,108,110,114,116,117 Oncologia pediátrica 180, 190…”
unclassified
“…Ainda há escassez de material publicado na literatura sobre esse tema. Embora tenham sido publicados trabalhos sobre as características técnicas dos equipamentos (10,11) , sobre o treinamento no método (12) e sobre a influência da qualidade das imagens em determinados diagnósticos (13)(14)(15) , um dos poucos artigos escritos nesta linha, foi o método proposto por este grupo, batizado de SQUALUS -Sistema Quantitativo de Avaliação da Qualidade de exames Ultrassonográficos. (16) Pelo método proposto no artigo original, a avaliação da qualidade das imagens documentadas verificava inicialmente se o número de imagens e estruturas registradas seguiram protocolos pré-determinados por órgãos como o Colégio Brasileiro de Radiologia (CBR) ou pelo American College of Radiology (ACR) ou ainda pelo American Institute of Ultrasound in Medicine (AIUM).…”
Section: Introductionunclassified
“…Fator de risco 13,27,29,114 Força muscular respiratória 12,13,14,17,19,21 O Obesidade 23,28,31,38,39,40,56,102,108,110,114,116,117 Oncologia pediátrica 180, 190…”
unclassified